PICES Press, Vol. 25, No. 2, Summer 2017 - North Pacific Marine Science Organization (PICES) (North Pacific Marine Science Organization (PICES), 2017)
2017 Inter-sessional Science Board Meeting (pp. 1-4); Highlights from the FUTURE SSC’s 3rd Inter-sessional Meeting (pp. 5-6); WG 35 (WG-NPESR3) meets inter-sessionally in Honolulu (pp. 7-8); PICES/ICES International Symposium on “Drivers of dynamics of small pelagic fish resources” (pp. 9-12); SPF Workshop on “Environmental control of spatio-temporal changes in population size, distribution and migration of small pelagic fish in an ecosystem context” (pp. 13-15); SPF Workshop on “Methods and techniques for sampling and assessing small pelagic fish populations” (16-17); SPF Workshop on “Modeling migratory fish behavior and distribution” (pp. 18-19); SPF Workshop on “Recent advances in the life stage ecophysiology of small pelagic fish” (pp. 20-21); SPF Workshop on “Remote sensing and ecology of small pelagics” (pp. 22-23); SPF Workshop on “Simulation approaches of forage fish populations for management strategy evaluations” (pp. 24-26); An ICES/PICES Workshop on “Understanding the impacts and consequences of ocean acidification for commercial species and end-users” (pp. 27-28); The 26th International Hydrological Program (IHP) training course on “Coastal vulnerability andfreshwater discharge” (pp. 29-30); PICES/MAFF MarWeb project collaborates with the United Nations program on the development of Marine Protected Areas in Guatemala (pp. 31-34); Program of topic sessions and workshops at PICES-2017 (pp. 35-35); The 3rd PICES/ICES Early Career Scientist Conference takes place in Busan, Korea (pp. 36-39); The Bering Sea: Current status and recent trends (pp. 40-42); The state of the western North Pacific during the 2016 warm season (pp. 43-44)